Detecting Traffic Differentiation in Backbone ISPs with NetPolice - Zhang, Ying; Mao, Z. Morley; Zhang, Ming (IMC, 2009)
Trafﬁc differentiations are known to be found at the edge of the Internet in broadband ISPs and wireless carriers [13, 2]. The ability to detect trafﬁc differentiations is essential for customers to develop effective strategies for improving their application performance. We build a system, called NetPolice, that enables detection of content- and routing-based differentiations in backbone ISPs. NetPolice is easy to deploy since it only relies on loss measurement launched from end hosts. The key challenges in building NetPolice include selecting an appropriate set of probing destinations and ensuring the robustness of detection results to measurement noise. We use NetPolice to study 18 large ISPs spanning 3 major continents over 10 weeks in 2008. Our work provides concrete evidence of trafﬁc differentiations based on application types and neighbor ASes. We identify 4 ISPs that exhibit large degree of differentiation on 4 applications and 10 ISPs that perform previous-AS hop based differentiation, resulting in up to 5% actual loss rate differences. The signiﬁcance of differences increases with network load. Some ISPs simply differentiate trafﬁc based on port numbers irrespective of packet payload and the differentiation policies may only be partially deployed within their networks. We also ﬁnd strong correlation between performance differences and Type-of-Service value differences in the trafﬁc.